Numerical Study on the Influence of Thermophores and Magnetic Field on the Boundary Layer Flow Over a Moving Surface in a Nanofluid - Hussaini, A.; Madaki, A. G.; Alaramma, S.K.; Barde, A.; Abdulkadir Tata, Adamu (International Journal of Scientific Research and Modern Technology, 2022)
For the present research, an attempt was made to study the influence of magnetic field and thermophoresis on an existing mathematical model. The impacts made by both magnetic parameter and thermophoresis over the nanofluids flux as well as the characteristics of transfer of heat are studied and analyzed by using a suitable numerical method (Runge- Kutta- Fehlberg method together with shooting technique) in maple2020. Also the effects of some emerging physical parameters on the profiles of momentum and temperature have been studied and analyzed in tables and graphs. Two solutions are obtainable if the free stream and the plate moves conversely to each other. At the end it was found that the Nusselt number is mostly an increasing function, whereas, the momentum and the temperature fluctuates with different parameters.